Estudo dos óxidos A2B2O7 e ABO3 a base de terras raras, para aplicações térmicas e catalíticas a altas temperaturas - Lopes, Francisco Wendell Bezerra (2011)
Rare earth elements have recently been involved in a range of advanced technologies like microelectronics, membranes for catalytic conversion and applications in gas sensors. In the family of rare earth elements like cerium can play a key role in such industrial applications. However, the high cost of these materials and the control and efficiencies associated processes required for its use in advanced technologies, are a permanent obstacle to its industrial development. In present study was proposed the creation of phases based on rare earth elements that can be used because of its thermal behavior, ionic conduction and catalytic properties. This way were studied two types of structure (ABO3 and A2B2O7), the basis of rare earths, observing their transport properties of ionic and electronic, as well as their catalytic applications in the treatment of methane. For the process of obtaining the first structure, a new synthesis method based on the use of EDTA citrate mixture was used to develop a precursor, which undergone heat treatment at 950 ° C resulted in the development of submicron phase BaCeO3 powders. The catalytic activity of perovskite begins at 450 ° C to achieve complete conversion at 675 ° C, where at this temperature, the catalytic efficiency of the phase is maximum. The evolution of conductivity with temperature for the perovskite phase revealed a series of electrical changes strongly correlated with structural transitions known in the literature. Finally, we can establish a real correlation between the high catalytic activity observed around the temperature of 650 ° C and increasing the oxygen ionic conductivity. For the second structure, showed clearly that it is possible, through chemical processes optimized to separate the rare earth elements and synthesize a pyrochlore phase TR2Ce2O7 particular formula. This "extracted phase" can be obtained directly at low cost, based on complex systems made of natural minerals and tailings, such as monazite. Moreover, this method is applied to matters of "no cost", which is the case of waste, making a preparation method of phases useful for high technology applications